The relationship of the structural patterns of grade four social studies textbooks to the structural patterns in English in grade IV - Morcozo, Adelaida Vizcaya 1930- (s.n.], 1971)
The study sought to determine whether the linguistic structures taught in grade four oral English based on the language textbook are the same patterns used in the social studies textbooks. The central hypothesis verified was: there is no difference between the kinds and frequency of use of the patterns of syntax that appear in grade four social studies textbooks and English in Grade IV.